Serum myokines as potential biomarkers of myostatin inhibition in sport doping: a preliminary study on their baseline levels in elite athletes - Francesco Donati; Giorgia Morgan Biasini; Xavier de la Torre; Francesco Botrè (Termedia Publishing House, 2023)
We considered in this study the possibility of developing an indirect procedure for detecting myostatin inhibition/suppression, a practice that is prohibited as doping in sport. We have specifically considered the potential diagnostic utility of human serum myokines as indirect markers of myostatin inhibition. Myostatin, its main antagonist follistatin, and other myokines (follistatin-like 1, musclin, oncostatin, osteonectin, irisin, brain derived neurotrophic factor, and insulin-like growth factor-1) were selected as a panel of potential biomarkers whose levels may be altered following myostatine suppression. The serum levels of myostatin and of the nine myokines were measured in elite athletes of different age, sex, and sport discipline, and their cross correlation assessed by multivariate analysis. All myokines resulted to be measurable in human serum, except for musclin and irisine, whose levels were below the limits of quantitation in a reduced number of samples. Serum concentrations varied of different orders in magnitude (musclin and osteonectin 10 ng/mL), while no significant differences were found between female and male subjects, with the exceptions of follistatin-like 1 and musclin, showing a higher concentrations in females ( p < 0.05). Levels of insulin-like growth factor 1 and brain derived neurotrophic factor were significantly higher in power athletes than in endurance ones. Multivariate statistics showed that musclin, follistatin-like 1 and oncostatin are more clustered and correlated to myostatin than other myokines, suggesting they could be considered as potential biomarkers of doping by myostatin inhibitors.